Вплив аутовакцини на основі пептидоглікану Staphylococcus аureus Wood 46 на динаміку росту експериментальних пухлин у мишей - Позур, В.В.; Сківка, Л.М.; Потебня, Г.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The effect of peptidoglycan from Staphylococcus aureus Wood 46 and cancer autovaccine supplemented with PG on the growth of experimental tumors in mice is investigated. It is shown that bacterial peptidoglycan both alone and as a part of the cancer autovaccine inhibits the growth of tumors. The cancer autovaccine with PG had the most supressive effect on the Lewis lung carcinoma growth: tumor sizes in experimental animals were by 37% smaller than those in control.